Constructing and using a light trap harvester: Rural Technology for mass collection of Agoro termites (“Macrotermes subhylanus”) - Ayieko, Monica A.; Obonyo, G.O.; Odhiambo, J.A.; Ogweno, P.L.; Achacha, J.; Anyango, J. (Airit Library, 2011)
Entomophagy is now a growing industry in many parts of the world especially in the developing countries. Entrepreneurs in several parts of the world are making edible insects both palatable and marketable for income generation. The traditional use of insects as food continues to be widespread in tropical and subtropical countries and to provide significant nutritional, economic and ecological benefits for rural communities. Consumption of insects is considered to be a more efficient use of the world's resources to feed the growing population. Insect consumption is growing in many parts of the world and the winged termite in particular is consumed widely in various part of East Africa especially in the western part of Kenya. The traditional methods of collecting these termites vary considerably from one region to another. This paper highlights the indigenous ways of collecting Macrotermes subhylanus locally known as Agoro in the Lake Victoria region. The method was developed by integrating modern technology and the indigenous technological knowledge. The variation in the yield of the sample of Agoro mounds selected and the traps used are presented and discussed.
Keywords: Agoro; Harvesters; indigenous knowledge; Termites; Yields